Instructive manual and teacher's guide to english teaching at Guaca Arriba Elementary School - Loo M., Evans Enrique (UDELAS, 2011)
We decided to elaborate a student manual and teacher's guide according with their english knowledge level as an important tools that will help the teacher and students since 2011.